Retaliation against the outgroup: The role of self-uncertainty. (August 2019) - Niedbala, Elizabeth M.; Hohman, Zachary P.
Outgroups who threaten the core aspects of one's identity, such as one's social group and its values, may make group members feel self-uncertain. Because past research associates uncertainty with defensive behavior, we propose that self-uncertainty will drive aggressive retaliation against a threatening outgroup. Two experiments tested the role of self-uncertainty in retaliation motivation. In Experiment 1, university students were threatened by their school rival and then reported self-uncertainty and willingness to retaliate. The threat evoked anger and caused male group members to feel significantly more self-uncertain, which was associated with significantly greater retaliation motivation. In Experiment 2, we manipulated Americans' feelings of self-uncertainty and threat from a terrorist group, ISIS. Uncertain males were significantly more willing to retaliate against ISIS after threats that caused anger and fear. For male group members, outgroup threat increases self-uncertainty, which then motivates them to be more willing to violently retaliate.